RETHINKING THE ‘TRUTH’ OF IDENTITY: DISSECTING QUEERNESS AND EMO SUBCULTURE IN NETFLIX’S THE UMBRELLA ACADEMY - Pradipta Michella Wibrinda (Universitas Gadjah Mada, 2021)
Over the years, the presence of LGBTQ+ community in the media has gone through noticeable change. It is a challenge for online streaming services like Netflix to represent as many communities and subcultures as they can, because accessibility comes with more diverse audience. While many LGBTQ+ characters have been put in the spotlight, those who identify beyond binaries are still arguably underrepresented, especially the ones that belong to socially degraded subculture like emo. The Umbrella Academy is a TV show rooted in emo subculture that feature LGBTQ+ superhero characters, Klaus Hargreeves and Vanya Hargreeves, who do not fully associate with the label “gay”, “lesbian”, or “bisexual”. This study employs what Judith Butler asserts, that gender expressions and practices of desire go beyond binaries, to see how emo subculture engages queerness as rejection to rigid classification of gender identities and sexual practices, as well as a tool to oppose conservatism, especially of previous generations. The discussion reveals that contrary to the popular belief that perceives emo as the culture of straight middle-class white boys, the show perceives emo subculture through the characters’ rejection to absolute identification. The characters show rejection through clothing, behavior, mannerism, and verbal statements. The characters also show opposition to conservatism, which include traditional gender roles, traditional superhero narratives, masculine-feminine polarity, and the ‘truth’ of identity.